Surveillance of neutralizing antibodies against Bovine Herpesvirus 1 in cattle herds from different farming property systems (Bioscience Journal, 2014)
The aim of this study was to investigate the presence of neutralizing antibodies against bovine herpesvirus 1 (BoHV-1) in 722 non-vaccinated animals from eight properties that use different farming systems (extensive, semi-confinement and confinement). Serum samples were subjected to neutralization tests in order to search for anti-BoHV-1 antibodies. Serological results were categorized as negative, low titer, intermediate titer or high titer. One property showed no positive samples; while other properties presented frequency of positive samples ranging from 17.95% to 86.96%. For animals raised under confinement, the number of positive samples and neutralizing antibody titers were lower compared to others, possibly due to good sanitary practices adopted by this type of system. Altogether, our results can contribute towards the understanding of the endemic infection in Brazil.